Pemikiran Ekonomi Ilmuwan Muslim Indonesia (Cokroaminoto, Syfrudin Prawiranegara, Moh. Hatta, H. Abdul Malik Karim Amrullah) - Minkhatul Maula; Ridwan Abu Djibran; Angga Candra Winata; Muhammad Taufiq Abadi; Muhammad Aris Syafi’i (CV. KAMPUS AKADEMIK PUBLISING, 2024)
At various moments, Islamic economic philosophy has developed thinking that is unique to each hour. The Islamic economic theory that developed during the independence period was different from the pre-independence and Old Order Islamic economic theories. The perspective of Islamic economic theory during the Old Order was also different from its perspective during the New Order. Similarly, Islamic economic theory developed during the New Order era has differences with post-New Order Islamic economic theory. The purpose of this research is to find out the thoughts of Indonesian Muslim scientists (Cokroaminoto. Syafruddin Prawiranegara Moh. Hatta, and H. Abdul Malik Karim Amrullah) in the field of economics. This journal is compiled through a literature study using content analysis techniques from sources such as books, journals, and articles on the economic thoughts of Indonesian Muslim scholars. The results show that there are differences among these figures in terms of the level of experience and practical implementation of activities in the field of economics among Indonesian Muslim scholars.